Summative Assessment and Formative Assessment of Online Learning - Ade Hera Adinda; Hossiana Ekklesia Siahaan; Inas Fawaz Raihani; Naurah Aprida; Niken Fitri; Ade Suryanda (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Sukabumi, 2021)
Assessment is an essential part of offline and online learning, especially when determining student learning results. Each learning process requires an assessment to ensure the learning objectives are achieved. Assessment is also needed as a form of teacher accountability. The assessments that can be done in the learning process are formative and summative. This assessment uses a literature research method where the data obtained comes from literature or literature that examines summative assessment and formative assessment of online learning. In online learning environments, formative and summative assessment methods require more consideration. Formative and summative assessments are used to assess students' views on online learning. Making an assessment for online education, whether formative or summative, also requires the function of related principles and objectives. Formative assessment is carried out while the technique of learning and teaching activities of a particular unit/competency is underway. Formative assessment has the purpose of knowing the development of learner mastery of the unit/competency that is being studied. Summative assessment is accessible in online learning classes because it can efficiently determine the value of student learning outcomes. Summative assessment is usually done at the end of the learning process. The purpose of summative assessments is to understand how much the student's achievement of the studies has been completed. This article will provide an overview of formative and summative assessment methods suitable for online learning environments.